1995
DOI: 10.1002/mrd.1080400405
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and tissue‐specific expression of human CD4 in transgenic rabbits

Abstract: A major obstacle to understanding AIDS is the lack of a suitable small animal model for studying HIV-1 infection and the subsequent development of AIDS, and for testing diagnostic, therapeutic, and preventive modalities. Our goal is to produce a rabbit model for the study of AIDS. Here we report on the generation of transgenic rabbits that express the human CD4 (hCD4) gene. The transgene, which contains the coding region for hCD4 and approximately 23 kb of sequence upstream of the translation start site, was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
4
15
0
Order By: Relevance
“…On the other hand, we found no difference in the number of newborn rabbits after embryo transfer of SM or DM-derived embryos, 24-26%. This survival rate is similar or higher than that described earlier using SM (Snyder et al, 1995, Murakami & Imai, 1996, Chrenek et al, 2002. Altogether, the results in mice showed a reduced viability of DM (25%) compared to SM (32%) embryos depending on the transgene Non-injected 35 3 2/3 (67%) 5 Kupriyanov et al, 1998).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…On the other hand, we found no difference in the number of newborn rabbits after embryo transfer of SM or DM-derived embryos, 24-26%. This survival rate is similar or higher than that described earlier using SM (Snyder et al, 1995, Murakami & Imai, 1996, Chrenek et al, 2002. Altogether, the results in mice showed a reduced viability of DM (25%) compared to SM (32%) embryos depending on the transgene Non-injected 35 3 2/3 (67%) 5 Kupriyanov et al, 1998).…”
Section: Discussionsupporting
confidence: 83%
“…Transgene integration efficiency in rabbits has been reported to range between 2 and 31%, depending on the gene construct and its concentration. Hammer et al, (1985) reported a 13% integration efficiency of the hGH gene into the rabbit genome, Snyder et al, (1995) about 18% with the hCD4 gene, Hirabayashi et al, (2000) a 4-8% efficiency with the hGH gene, Murakami et al, (2002) a 31% efficiency with hCD55 gene, Chrenek et al, (2002) about 3% with the hPC gene, Hiripi et al (2003) about 2% with hFVIIIMt gene and Lipinski et al, (2003) about 4.5% with the hGH gene. In this study we also present different efficiencies of integration of two different gene constructs, hFVIII and EGFP, and two techniques of microinjection carried out on the same equipment by a single investigator.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless to our knowledge, the 18 offspring obtained in the present study were the ®rst rabbits to develop from cryopreserved pronuclearstage zygotes. The overall ef®ciency of producing transgenic rabbits by DNA injection of fresh zygote was 0.7% in the present study, within the range of 0.3 to 2.5% reported to date (Snyder et al, 1995;Spieker-Polet et al, 1995;Aigner et al, 1996;Hirabayashi et al, 2000bHirabayashi et al, , 2001). Although we were unable to produce transgenic rabbits from cryopreserved pronuclear-stage zygotes in the present study, our results do not necessarily lead to the conclusion that cryopreserved pronuclear-stage rabbit zygotes will not be useful for production of transgenic rabbits by DNA microinjection.…”
Section: Discussionsupporting
confidence: 60%
“…However, the high magnitude g force on the pronuclear zygotes themselves was reported not to be detrimental to their subsequent developmental potential in rabbits [11], pigs [39] and cattle [38]. The reduction in the developmental potential of the DNA-injected zygotes is known in mice [2,3,19,22,34], rats [4,5,13,15,17,20,23,32], rabbits [8,21,30,31,39] and pigs [8,24,27,28,36] to be from one-third to one-half of nontreated zygotes. In the present study, the maximum number of zygotes transferred into each recipient was the same in the four examined species and most of the recipient animals (13 of 13, 100% in mice; 15 of 15, 100% in rats; 8/11, 73% in rabbits; 7 of 9, 78% in pigs) became pregnant by the surgical transfer of the DNAinjected zygotes.…”
Section: Discussionmentioning
confidence: 99%
“…In the production of transgenic mice it was reported that 0.5 to 10.0% of the DNA-microinjected zygotes developed into offspring carrying exogenous DNA [2,3,19,22,34]. A range of 0.4 to 4.8% of the DNAmicroinjected rat zygotes were reported to develop into transgenic rats [4,13,15,17,20,32], and in rabbits and pigs, 0.3 to 2.6% [1,18,21,30,31] and 0.3 to 1.4% [8,[27][28][29]36] of the DNA-microinjected zygotes developed into the transgenic animals, respectively. However, concluding that the efficiency of producing transgenic animals is dependent on the body size of the animals based on these reports is problematic, because a great variety of exogenous DNA constructs and technical protocols for DNA microinjection were employed in each laboratory.…”
Section: Introductionmentioning
confidence: 99%